2011
DOI: 10.1007/s00464-011-1861-4
|View full text |Cite
|
Sign up to set email alerts
|

Visual force feedback in laparoscopic training

Abstract: BackgroundTo improve endoscopic surgical skills, an increasing number of surgical residents practice on box or virtual reality (VR) trainers. Current training is focused mainly on hand–eye coordination. Training methods that focus on applying the right amount of force are not yet available.MethodsThe aim of this project is to develop a low-cost training system that measures the interaction force between tissue and instruments and displays a visual representation of the applied forces inside the camera image. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 8 publications
0
53
0
Order By: Relevance
“…Although the literature is generally scarce in this field, the group from the Delft University of Technology showed a tendency to favor mean absolute nonzero force. 20,21 In comparing multiple variables of force, we found that the difference in mean force among experience groups was less important than other variables investigated. We hypothesize that this is owing to bias introduced by increased time that nonexperts spend in the ''idle'' state that brings down any central tendency value.…”
Section: Discussionmentioning
confidence: 90%
“…Although the literature is generally scarce in this field, the group from the Delft University of Technology showed a tendency to favor mean absolute nonzero force. 20,21 In comparing multiple variables of force, we found that the difference in mean force among experience groups was less important than other variables investigated. We hypothesize that this is owing to bias introduced by increased time that nonexperts spend in the ''idle'' state that brings down any central tendency value.…”
Section: Discussionmentioning
confidence: 90%
“…As needle‐driving in this study was only a part of the total task, it seems that trainees were satisfied when the needle had been driven through the tissue successfully and then focused on the more complex knot‐tying part of the task. Because the complete suture task requires a larger cognitive component than the needle‐driving task alone, it is likely that a greater focus on forces exerted on the needle during the short needle‐driving phase results in a greater reduction in force, as shown previously. This suggests that complex tasks should be divided into smaller, simpler tasks, which are trained individually to create optimal learning circumstances.…”
Section: Discussionmentioning
confidence: 93%
“…This included a force sensor to measure time and force in laparoscopic box trainers ranging from 0 to 10 N in three dimensions, with an accuracy of 0·1 N and a measurement frequency of 60 Hz. A webcam was used to capture images of the work space of the instruments. A box trainer illuminated to simulate laparoscopic surgery was equipped with two trocars and two needle drivers (Ethicon E705R 5 mm; Johnson & Johnson, Norderstedt, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The ForMoST hybrid trainer is equipped with the TrEndo tracking system, the ForceTRAP force tracking system and an USB camera for the visualization of the task on the computer screen [18]. The ForMoST system measures all instrument movement and forces exerted on the training task.…”
Section: Methodsmentioning
confidence: 99%